#blessed and the fancy self: An Exploratory Study on the Different “Selves” Constructed in Facebook Posts - Sequeton, Grace M. (Journal of English Studies and Comparative Literature, 2019)
Social networking sites have become so popular that almost everyone is on Facebook or Twitter or Instagram, or on all three. These sites have become an avenue for meeting new people and for reconnecting with old friends and long-lost relatives. Because of the public nature and the wide reach of these sites, online users feel the need to present themselves in a positive light and create a good impression on the other online participants. This kind of self-presentation can be observed through online interaction or in posts and status updates. This paper then explores the different ways of self-presentation made by Facebook users when they use #blessed in their posts. Through the hashtag, a self-image that is beyond the denotative meaning of the word blessed is constructed. It is hard to reconcile the religious association of the word blessed and the text (linguistic andvisual) that shows how thankful they are for the luxury they enjoy. Using Goffman’s theories on dramaturgy and impression management, this paper will analyze the captions that accompany the photos posted as textual evidence to see how the use of #blessed has become an accessory that is available to the self in his/her need and/or want to curate and engineer an ideal version of himself/herself.